THE CONTRIBUTION OF PHOTOVOLTAICS ON “CARBON NEUTRAL” BUILDINGS IN REDUCING CO₂ EMISSIONS - Tsamara, Vonny; Chona'ah, Rizki (Border: Jurnal Arsitektur, 2020)
The formation process of a building from the construction phase up to the use of building require much energy. It triggers the happening of global warming. Although the concept of building sustainability applies from now on, but the effect is considerably less, because it doesn’t concern the energy used that consumes on the construction phase. This scientific article is about the effort of reducing the carbon footprint through the concept of carbon neutral that allows the carbon consumption of building returns to zero point by the CO₂ emission reduction in electrical energy consumption. The method is summative evaluation on the architectural work of The Glaxo Smith Kline Carbon Neutral Laboratories for Sustainable Chemistry at Nottingham University to reviewing the electrical energy consumption from the construction phase to the use of the building. The result of this method is proving the building that use photovoltaic technology, which change the sunlight into electrical energy contributes 60,2% of the total electrical energy needs on the effort of CO₂ emission reduction through the systems which the excess energies produced are as carbon credits for “paying back” the carbon used during the construction phase. Through this building, human, nature and technology can walk in harmony without being second-numbered.